2020
DOI: 10.1093/brain/awaa313
|View full text |Cite
|
Sign up to set email alerts
|

When affect overlaps with concept: emotion recognition in semantic variant of primary progressive aphasia

Abstract: The most recent theories of emotions have postulated that their expression and recognition depend on acquired conceptual knowledge. In other words, the conceptual knowledge derived from prior experiences guide our ability to make sense of such emotions. However, clear evidence is still lacking to contradict more traditional theories, considering emotions as innate, distinct and universal physiological states. In addition, whether valence processing (i.e. recognition of the pleasant/unpleasant character of emot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(23 citation statements)
references
References 88 publications
1
22
0
Order By: Relevance
“…While both age groups showed an overall decrement in valence as more words were generated, this decrease was steeper in the group of younger adults, as indicated by a significantly stronger coefficient of negative correlation. Experimental evidence indicates that there is a close relationship between SM and valence attribution ( Bertoux et al, 2020 ). Other than showing consolidated semantic-memory skills ( Nyberg et al, 1996 , 2003 ; Park et al, 2002 ; Verhaeghen, 2003 ; Rönnlund et al, 2005 ; Small et al, 2011 ), older adults also show an “age-related positivity” effect, whereby stimuli of positive value have a processing advantage over stimuli of negative value ( Reed and Carstensen, 2012 ).…”
Section: Discussionmentioning
confidence: 99%
“…While both age groups showed an overall decrement in valence as more words were generated, this decrease was steeper in the group of younger adults, as indicated by a significantly stronger coefficient of negative correlation. Experimental evidence indicates that there is a close relationship between SM and valence attribution ( Bertoux et al, 2020 ). Other than showing consolidated semantic-memory skills ( Nyberg et al, 1996 , 2003 ; Park et al, 2002 ; Verhaeghen, 2003 ; Rönnlund et al, 2005 ; Small et al, 2011 ), older adults also show an “age-related positivity” effect, whereby stimuli of positive value have a processing advantage over stimuli of negative value ( Reed and Carstensen, 2012 ).…”
Section: Discussionmentioning
confidence: 99%
“…The current findings allow only for qualitative comparison between these groups. A recent study of 16 SD patients provided evidence of correlations between category fluency performance, facial emotion recognition ability, and conceptual and taxonomic knowledge about emotion (Bertoux et al, 2020). Future research with a similarly large sample of both SD and SA patients could be helpful in understanding the effects of both the nature and severity of semantic impairment on emotion categorization deficits.…”
Section: Limitationsmentioning
confidence: 96%
“…Patients who had difficulty identifying specific emotions in faces were more likely to have degeneration in regions of the brain associated with semantics such as the vlPFC and temporal pole. More recently, Bertoux et al (2020) demonstrated that semantic fluency and conceptual knowledge about emotion predicted deficits in facial emotion perception in patients with semantic dementia, an effect associated with neurodegeneration in ventral frontal and temporal regions and changes to white matter tracts linking frontal and temporal cortices.…”
Section: Brain Regions Involved In Semantic Processing Are Necessary For Emotion Differentiationmentioning
confidence: 99%